Analysis Of Biomass Of Mucuna Bracteata DC Due To The Provision Of Coffee Skin Waste As An Alternative Fertilizer - Tarigan, Andry Admaja; Perangin-angin, Hagai Jorenta; Afrianti, Suratni; Sulastri, Yustina Sri; Sihaloho, Martha Adiwaty; Pratomo, Bayu (Prodi Agroteknologi Fakultas Agro Teknologi Universitas Prima Indonesia, 2025)
Biomass Analysis of Mucuna bracteata DC Due to the Application of Coffee Husk Waste as an Organic Nutrient Source. Mucuna bracteata DC is a cover crop that plays a crucial role in soil conservation and soil fertility improvement. This study aims to analyze the effect of liquid organic fertilizer (LOF) derived from coffee husk waste on the biomass growth of Mucuna bracteata DC, particularly in terms of fresh shoot weight, fresh root weight, dry shoot weight, and dry root weight. The research was conducted at Jalan Kuali No. 50, Medan Petisah District. The experiment was designed using a Completely Randomized Block Design (CRBD) with a single-factor treatment consisting of seven LOF dosage levels: K0 (no treatment), K1 (5 mL/polybag), K2 (10 mL/polybag), K3 (15 mL/polybag), K4 (20 mL/polybag), K5 (25 mL/polybag), and K6 (30 mL/polybag), with four replications, totaling 28 experimental plots. The results showed that the application of coffee husk LOF significantly affected the biomass growth of Mucuna bracteata DC. The highest fresh shoot weight (9.51 g) and dry shoot weight (2.14 g) were recorded in treatment K6 (30 mL/polybag), whereas the highest fresh root weight (2.29 g) and dry root weight (0.32 g) were observed in treatment K5 (25 mL/polybag). Higher LOF doses generally increase plant biomass up to an optimal threshold, beyond which nutrient absorption efficiency by roots declines. Overall, the optimal LOF dosage for maximizing biomass growth in Mucuna bracteata DC ranges between 25–30 mL/polybag. The use of coffee husk waste as an organic nutrient source presents a sustainable alternative for improving plant productivity while reducing dependency on synthetic fertilizers.